Efecto de la inclusión de harina de hojas de moringa en la dieta del Chame - Rosales Zambrano, Amy Valkyria (2022)
This research was carried out in the Experimental Farm "La María", owned by the UTEQ, located in the canton Mocache, province of Los Ríos. It lasted 63 days in which the proximal composition of the prepared diets and the zootechnical parameters of the fry were determined. Diets formulated with moringa leaf meal, each treatment at different percentages, were used 12 experimental cages in which 10 chame fry were placed (Dormitator latifrons). Biometries were performed every 7 days analyzing the productive behavior of the fry feeding them with the diets elaborated during a period of 63 days, used a Complete Random Design (CRD) for 4 treatments and three repetitions. The fry were acclimatized for 15 days, during which time they were dewormed. At the end of the experiment, an increase in protein was observed with the inclusion of moringa leaf meal in the diets prepared, while in the zootechnical variables, it was noted that the best treatment in terms of weight and size was treatment 2, compared to the control treatment, which presented a smaller size; the survival percentage was 100 in each of the treatments.